ANALISIS PROFITABILITAS PADA PT. NIPPON INDOSARI CORPINDO TBK PERIODE TAHUN 2015-2017 - Maisyarah Maisyarah; Erni Setiawati; Pantas P. Pardede (OBOR: Oikonomia Borneo, 2019)
This study aims to determine the financial profit of a company PT. Nippon Indosari Corpindo Tbk Period 2015-2017 by comparing the average industry of similar companies.The results of the analysis, note that PT. Nippon Indosari Corpindo Tbk seen from the Gross Profit Margin ratio is above the industry average of similar companies which illustrates that PT. Nippon Indosari Corpindo Tbk is better than the industry average of similar companies, the net profit margin ratio in the 2015 period is above the industry average of similar companies, but the period 2016-2017 is below the industry average of similar companies. While the Return on Investment ratio at PT. Nippon Indosari Corpindo Tbk is below the industry average value of similar companies which illustrates that PT. Nippon Indosari Corpindo is inefficient in the ratio of Return on investment, the ratio of Return on Equity for the period of 2015 is above the average industry of similar companies, but the period 2016-2017 PT. Nippon Indosari Corpindo Tbk is below the industry average of similar companies. Keywords: Financial Management, Financial Statements, Financial Ratios, Profitability, Gross Profit Margin (GPM), Net Profit Margin (NPM), Return On Investment (ROI), Return On Equity (ROE), Industry Ratios.